Prospects for use of smart meters to reduce electricity losses in Ukraine’s power grids - L. Mikhailova; V. Dubik; O. Kozak; O. Gorbovy (Machinery & Energetics, 2025)
The aim of this study was to determine the potential for reducing technical and commercial electricity losses through the integration of smart metering technologies into the existing distribution network infrastructure. The research employed scenario modelling, systems analysis, structural-functional comparison, and an examination of international experience. The level of electricity losses in Ukraine as of 2024 was analysed and found to be 18-19% of the total energy generated, with approximately 70% of these losses being technical in nature. The structure of electricity generation was found to comprise nuclear (55%), thermal (24%), hydro (9%), solar (7%), and wind (5%) energy. It was revealed that partial deployment of smart meters at a 50% penetration rate could reduce losses by 25%, while full coverage of the distribution network could reduce them by up to 45%. The technical characteristics of smart meters were summarised, including high-frequency data collection at 15-minute or hourly intervals, remote real-time data transmission via mobile networks or Power Line Communication (PLC) systems, and automatic detection of emergency situations and unauthorised interference. It was demonstrated that integrating smart meters with energy management systems enables effective load balancing, reduced peak demand, and optimised electricity distribution. The experiences of the United States, the EU, and China were also reviewed, confirming the feasibility of large-scale deployment of such systems to reduce losses and stimulate the development of distributed generation. The findings highlight the promise of smart meters in the digital transformation of Ukraine’s energy system, enhancing its adaptability, reliability, and resilience to emerging challenges. The practical value of the study lies in developing approaches to digitalising electricity consumption metering in Ukraine, which could be utilised in modernising energy networks and forming a resilient smart energy system